Oscillation Detection in Process Industries by a Machine Learning-Based Approach - Dambros, Jônathan W. V; Trierweiler, Jorge O; Farenzena, Marcelo; Kloft, Marius (Industrial & engineering chemistry research, 2019)
Oscillatory control loop is a frequent problem in process industries. Its incidence highly degrades the plant profitability, which means oscillation detection and removal is fundamental. For detection, many automatic techniques have been proposed. These are usually based on rules compiled into an algorithm. For industrial application, in which the time series have very distinct properties and are subject to interferences such as noise and disturbances, the algorithm must include rules covering all possible time series structures. Since the development of this algorithm is near impractical, it is reasonable to say that current rule-based techniques are subject to incorrect detection. This work presents a machine learning-based approach for automatic oscillation detection in process industries. Rather than being rule-based, the technique learns the features of oscillatory and nonoscillatory loops by examples. A model based on deep feedforward network is trained with artificial data for oscillation detection. Additionally, two other models are trained for the quantification of the number of periods and oscillation amplitude. The evaluation of the technique using industrial data with different features reveals its robustness.